An Orally Administered CeO2@Montmorillonite Nanozyme Targets Inflammation for Inflammatory Bowel Disease Therapy. (13th September 2020) - Zhao, Sheng; Li, Yixuan; Liu, Quanyi; Li, Sirong; Cheng, Yuan; Cheng, Chaoqun; Sun, Ziying; Du, Yan; Butch, Christopher J.; Wei, Hui
Abstract: Safe, effective, and convenient administration of therapeutic nanomaterials is one of the greatest difficulties in nanomedicine. To tackle this challenge, a system which couples multi‐enzyme mimicking CeO2 nanoparticles with clinically approved montmorillonite (MMT) for inflammatory bowel disease (IBD) therapy is reported. CeO2 exhibits superoxide dismutase‐ and catalase‐like activities, and hydroxyl radical scavenging activity, making it more efficient at scavenging reactive oxygen species (ROS) than non‐catalytic antioxidants while being more stable than free enzymes. In addition, negatively‐charged MMT can be orally administered and specifically adsorbed onto positively‐charged inflamed colon tissue via electrostatic interactions for targeted delivery. When the two are assembled together by in situ growth of CeO2 onto MMT, the optimized CeO2 @MMT(1:9) is stable in the stomach for oral delivery, targets the inflamed colon through electrostatic interactions, and reduces inflammation through ROS scavenging, all without any significant systemic exposure as demonstrated by the relief of murine IBD in vivo. Abstract : Orally administered CeO2 @MMT nanozymes couple multi‐enzyme‐like CeO2 nanoparticles (CeO2 NPs) with clinically approved montmorillonite (MMT) for inflammatory bowel disease therapy. The negatively charged MMT localizes the CeO2 @MMT to the positively charged inflamed colon where the catalytic CeO2 NPs deplete radical oxygen species thereby reducing inflammation. CeO2 @MMT remains bound to MMT, greatly reducing the bioavailability and nanotoxicity of CeO2 NPs.